Molecular Characterization of a Transcriptional Regulator GntR for Gluconate Metabolism in Industrial 2-Ketogluconate Producer Pseudomonas plecoglossicida JUIM01 - Mengxin Qu; Lulu Li; Xinyi Zan; Fengjie Cui; Lei Sun; Wenjing Sun (Microorganisms, 2025)
The GntR is a transcriptional regulator generally known as a gluconate-operon repressor to specifically regulate the transportation and phosphorylation of gluconate. In the present study we report the cloning of the GntR-encoding gene of the industrial 2-ketogluconate (2KGA)-producer Pseudomonas plecoglossicida JUIM01, which is involved in the regulation of gluconate metabolism, along with the identification of some of its target genes and its operator sequence. GntR is a 36.36-kDa cytoplasmic and hydrophobic DNA-binding transcriptional regulator belonging to the LacI family. The knockout of gntR resulted in the significant upregulation of the transcription of the gluconate kinase gene gntK and, to a lesser extent, the permease gene gntP, as well as downregulation of genes involved in glucose uptake (oprB-1, gltB, gltF, gltG, and gltK) and those involved in 2-ketogluconate (2KGA) transport (kguT) and catabolism (kguE, kguK, and kguD). These results indicated that GntR positively regulated glucose and 2KGA transport and catabolism, while negatively affecting GntP-mediated gluconate uptake and gluconate phosphorylation by GntK. Electrophoretic mobility shift assay (EMSA) and DNase I footprinting analyses confirmed that GntR interacted with operator sequences in the divergent promoter regions of gntK and gntP, as well as in the gntR promoter region. A putative operator sequence (consensus 5′-AG-N2-AGCGCT-N-TCT-3′) was identified. These data suggest that GntR positively regulates genes involved in glucose uptake/transport and 2KGA transport/catabolism, while repressing its own expression as well as that of genes involved in gluconate transport/catabolism. These findings not only elucidate the regulation of GntR and its target genes in P. plecoglossicida, but also provide valuable insights for optimizing industrial 2KGA production.